AN ANALYSIS OF THEME SYSTEM IN THE THREE TEXTS FROM ALEXANDER’S “DEVELOPING SKILLS” - Erna Rosmaida (Journal of English Education Program (JEEP), 2019)
This study will explore kinds of theme are found in the three texts and textual meaning which was created through the aplication of theme system in the three texts from the textbook entittled “Developing Skills” written by L.G. Alexander. This study employed a qualitative and discourse analysis as research design. The population of this study was all the text from “Developing Skills”. The findings revealed that kinds of theme system emerged in the first text was topical (unmarked and marked) and textual themes; in the second text also kinds of theme system was topical (unmarked and marked) and textual theme; and in the last text was topical (unmarked and marked), textual and interpersonal themes. All the texts dominated by topical unmarked theme. Textual meaning was created through the application of all theme system in the three texts that the author created coherent and cohesive texts. All of his texts were well- organized and focused. Based on the findings, it is recommended that theme – rheme be introduced and applied in the educational field because it can improve student’s skills, specifically reading and writing skills. Keywords: Systemic Functiona Grammar Perspective, Textual Meaning, Theme-Rheme, Discourse Analysis